(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
في هذا البحث ندرس إمكانية المساهمة في حلّ مسألة توجيه المركبة Vehicle Routing Problem (VRP)، وهي واحدة من مشاكل الأمثلية التي أخذت الكثير من الاهتمام في الوقت الحاضر بسبب تطبيقاتها ذات الطابع اليومي ، والتي هي مشكلة من النوع NP-hard . ولا توجد حتى الآن خوارزمية تقدم لنا الحلّ الأمثل لهذه المشكلة بسبب تعقيد الزمن متعدد الحدود ، فكل الخوارزميات المستخدمة تعطي حلولاً قريبة من الحلّ الأمثل . سنعرض في بحثنا الخوارزمية الهجينة ( HA) Hybrid Algorithm على مرحلتين : في المرحلة الأولى يتم تطبيق خوارزمية المسح Sweep Algorithm (SW) ، وفي المرحلة الثانية يتم تطبيق خوارزمية نظام مستعمرة النمل (AC) Ant Colony Algorithm , مع خوارزمية البحث المحلي local search 3-opt ، ثم مقارنة الحلّ الناتج من هذا النهج الهجين مع نتائج تجارب قياسية معروفة لتحديد فعالية النهج المقدم . In this research, we are studying the possibility of contribution in solving the Vehicle Routing Problem (VRP), which is one of the optimization problems that, because of its Real Life applications, has attracted a lot of attention at the present time. It is a problem of the NP-hard type. However, because of the complication of polynomial time there is still no algorithm providing us with the optimal solution of this problem. All the used algorithms give solutions that are close to the optimal one . In this research, we will present the Hybrid Algorithm (HA) in two phases .In the first phase the Sweep Algorithm (SW) is applied, and in the second one the Ant Colony Algorithm and the local search 3-opt are applied. we will then compare the quality of the solution resulted from this hybrid approach with the results of well-known standard tests to determine the effectiveness of the presented approach .